Mechanobiological Principles Influence the Immune Response in Regeneration: Implications for Bone Healing - Knecht, Raphael S.; Bucher, Christian H.; Van Linthout, Sophie; Tschöpe, Carsten; Schmidt-Bleek, Katharina; Duda, Georg N. (Frontiers in Bioengineering and Biotechnology, 2021)
A misdirected or imbalanced local immune composition is often one of the reasons for unsuccessful regeneration resulting in scarring or fibrosis. Successful healing requires a balanced initiation and a timely down-regulation of the inflammation for the re-establishment of a biologically and mechanically homeostasis. While biomaterial-based approaches to control local immune responses are emerging as potential new treatment options, the extent to which biophysical material properties themselves play a role in modulating a local immune niche response has so far been considered only occasionally. The communication loop between extracellular matrix, non-hematopoietic cells, and immune cells seems to be specifically sensitive to mechanical cues and appears to play a role in the initiation and promotion of a local inflammatory setting. In this review, we focus on the crosstalk between ECM and its mechanical triggers and how they impact immune cells and non-hematopoietic cells and their crosstalk during tissue regeneration. We realized that especially mechanosensitive receptors such as TRPV4 and PIEZO1 and the mechanosensitive transcription factor YAP/TAZ are essential to regeneration in various organ settings. This indicates novel opportunities for therapeutic approaches to improve tissue regeneration, based on the immune-mechanical principles found in bone but also lung, heart and skin.